2003
DOI: 10.1111/j.1365-3059.2003.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel carlavirus from melon in Brazil

Abstract: Since 1999, a yellowing disease of melon ( Cucumis melo ) has been observed in the north-east region of Brazil. The symptoms, mainly seen on older leaves, include leaf mottling and yellowing, symptoms which are similar to those associated with criniviruses (Wisler et al ., 1998) or nutritional disorders. Deformation of leaves, stems and fruits was rarely observed, but the low sugar content had a high impact on fruit quality and value. The disease was transmitted from melon to melon (6/24) and to West Indian gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 1 publication
0
11
0
10
Order By: Relevance
“…Esses cultivos apresentam variabilidade genética para vários caracteres que podem ser utilizadas no melhoramento das culturas. (Oliveira et al, 2000;Moura et al, 2001) e vírus do amarelão, que vem causando sérios prejuízos na cultura do melão e cuja etiologia foi sugerida por Lima et al (2002) como um possível vírus da família Closteroviridae, gênero Crinivirus, embora de acordo com Nagata et al (2003Nagata et al ( , 2005 se trate de um vírus da família Flexiviridae, gênero Carlavirus.…”
unclassified
“…Esses cultivos apresentam variabilidade genética para vários caracteres que podem ser utilizadas no melhoramento das culturas. (Oliveira et al, 2000;Moura et al, 2001) e vírus do amarelão, que vem causando sérios prejuízos na cultura do melão e cuja etiologia foi sugerida por Lima et al (2002) como um possível vírus da família Closteroviridae, gênero Crinivirus, embora de acordo com Nagata et al (2003Nagata et al ( , 2005 se trate de um vírus da família Flexiviridae, gênero Carlavirus.…”
unclassified
“…Conforme Nagata et al, (2003) e Santos et al, (2004), o amarelão pode ocasionar prejuízos na produção e, principalmente, na qualidade dos frutos, pela redução do teor de °brix. Isso ocorre devido à redução da D. C. Dantas et al Tabela 7 -Valores médios de teor de sólidos solúveis totais de frutos pequenos e frutos grandes e médio de melão amarelo.…”
Section: Resultsunclassified
“…On the other hand, molecular studies demonstrated the presence of a new virus causing yellowing mosaic in melon (Nagata et al 2003). The virus genome was partially sequenced and the virus was named Melon yellowing-associated virus (MYaV) included in the genus Carlavirus, family Betaflexiviridae (Nagata et al 2005, King et al 2012.…”
Section: Melon Yellowingmentioning
confidence: 99%